Potentials of Organic Waste Conversion in a Green Campus Concept - Mujaahid, Faaris; Fauzi, Argi Mochamad; Syahputra, Ramadoni; Putra, Karisma Trinanda; Purwanto, Kunnu (Journal of Electrical Technology UMY, 2017)
Development of waste-to-energy plant is regarded as one of a solution to reduce fossil energy dependency and switch to another alternative energy sources, thus needs to be implemented immediately. Research on the potential of organic waste by taking case studies at UMY green campus program can be an illustration that in the future UMY can process this potential into an alternative renewable energy. This research was conducted by studying waste management and data collection methods, such as field observations, discussions with related parties about the waste cycle, and calculations with the concept of gasification. Calculation of biomass produced by organic waste is then supplied to the motor generator for electricity production. Annually, 31.8 tons of organic waste could produce 7.9 kiloliters of biomass and channel it to the power plant system for generating electricity energy as much as 5.3 MWh per year. This number equals to the electricity supply of five small-housing in Indonesian typical house.